The Influence of Organizational Culture on the Government Internal Control System And Its Impact on the Quality of Financial Information Systems in the Regional Revenue Agency of West Java Province - Wihatmono, Shantyo Raharjo; Suharman, Harry; ., Daryanto (Journal of Ecohumanism, 2025)
The purpose of this study was to see how the influence of organizational culture on the government internal control system and its impact on the quality of the financial information system. The sample was 126 people spread across 4 district/city representatives, samsat, and the Regional Revenue Agency Office of West Java Province. The results showed a significant positive effect of Organizational Culture on the Government Internal Control System within the Regional Revenue Agency of West Java Province. There was a significant positive effect of Organizational Culture on the Quality of Financial Information Systems within the Regional Revenue Agency of West Java Province, and there was a significant positive effect of the Government Internal Control System on the Quality of Financial Information Systems within the Regional Revenue Agency of West Java Province. Moreover, Organizational Culture affects the Government Internal Control System. It significantly impacts the Quality of the Financial Information System within the Regional Revenue Agency of West Java Province.